2007
DOI: 10.1055/s-2007-966652
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-related colitis (previously known as ”pseudolipomatosis“): a series of cases occurring in an epidemic pattern

Abstract: We report several cases of hydrogen peroxide-related colitis that occurred in an epidemic pattern in our gastrointestinal endoscopy center during a 2-month period in early 2007. During colonoscopy using sterilized endoscopes that had been flushed with hydrogen peroxide after the peracetic acid cycle, instantaneous effervescence and blanching (the "snow white sign") were observed on the intestinal mucosa when the water button was depressed. Biopsy specimens revealed features resembling a clinical condition whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 5 publications
1
26
1
2
Order By: Relevance
“…Gutterman et al [209] identified only eight studies "which reported numerous adverse outcomes to healthcare personnel associated with endoscope reprocessing", including one case report with asthma for workers using a peracetic acid and hydrogen peroxide based product. The most commonly-reported side effect of peracetic acid in patients is a form of colitis, previously known as pseudolipomatosis [210] , which is commonly induced by hydrogen peroxide and peracetic acid but occasionally also by glutaraldehyde [211] . The colitis is often self-limiting but sometimes requires medical treatment.…”
Section: Clinical Side Effects Of Peracetic Acidmentioning
confidence: 99%
“…Gutterman et al [209] identified only eight studies "which reported numerous adverse outcomes to healthcare personnel associated with endoscope reprocessing", including one case report with asthma for workers using a peracetic acid and hydrogen peroxide based product. The most commonly-reported side effect of peracetic acid in patients is a form of colitis, previously known as pseudolipomatosis [210] , which is commonly induced by hydrogen peroxide and peracetic acid but occasionally also by glutaraldehyde [211] . The colitis is often self-limiting but sometimes requires medical treatment.…”
Section: Clinical Side Effects Of Peracetic Acidmentioning
confidence: 99%
“…Esses mesmos achados já tinham sido descritos em seres humanos submetidos à aplicação retal de H 2 O 2 que desenvolveram quadros graves de colite, até mesmo com evolução fatal 42,43 . Quando se constata que a deficiência de AGCC é capaz de deflagrar a CE é lícito supor que a aplicação regular de AGCC no cólon excluso, restabelecendo o fornecimento de butirato, poderia restabelecer o equilíbrio do metabolismo celular, reduzindo a lipoperoxidação e, consequentemente, a lesão tecidual.…”
unclassified
“…A number of different pathogenetic mechanisms have been hypothesized for this condition, including intramucosal penetration of air by mechanical injury during insufflation, biopsy, or other procedures (3). Other authors have suggested that chemical injury by disinfectants, particularly hydrogen peroxide, contributes to the pathogenesis of these lesions (4,5). Here we report and discuss colonic pseudolipomatosis incidentally found in a series of patients undergoing routine colonoscopy and underline the endoscopic pattern and diagnostic difficulties.…”
Section: Introductionmentioning
confidence: 72%